Analisis Hubungan Pengetahuan Dan Perilaku Swamedikas Masyarakat Desa Tiong Keranjik, Kecamatan Belimbing Hulu, Kabupaten Melawi - Patrisia alviani; Hariyanto IH; Indri Kusharyanti (Journal of Innovative and Creativity, 2026)
Self-medication has become a serous problem among the public due to a lack of knowledge and behavior about self-medication. The percentage of West Kalimantan people practicing self-medication during the last month in 2022 was 86.81%. The purpose of this study was to analyze the level of knowledge and behavior of community self-medication in tiong keranjik village, belimbing hulu sub-district, melawi district and the relationship between the two. This research method is a descriptive cross sectional non-experimental research. The sampling technique used purposive sampling with a questionnaire measuring instrument that had passed ethical review and tested validity and reliability on 30 respondents. Data processing was carried out with the spearman rank correlation statistical test. The results of the study of 100 respondents showed that the level of knowledge of community self-medication behavior is included in the good category by 25%, moderate by 57% and less by 18%. The results of the spearman rank correlation test between knowledge and self-medication behavior showed a significance value of 0.000 with a correlations coefficient of 0.651, and a positive direction. It can be concluded that the majority of people have sufficient knowledge with appropriate behavior and there is a significant relationship between the level of knowledge and self-medication behavior in the community of tiong keranjik village with a strong and unidirectional correlation